2011
DOI: 10.1158/0008-5472.can-11-1702
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Transcription Factor KLF5 in the Context of p53 Ablation Drives Invasive Progression of Human Squamous Cell Cancer

Abstract: Squamous cell cancers account for more than half of all human cancers, and esophageal cancer is the sixth leading cause of cancer death worldwide. The majority of esophageal squamous cell carcinomas have identifiable p53 mutations, yet the same p53 mutations are found at comparable frequencies in pre-cancerous dysplasia, indicating that transformation requires additional somatic changes yet to be defined. Here we show that the zinc finger transcription factor KLF5 transactivates NOTCH1 in the context of p53 mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(70 citation statements)
references
References 51 publications
(76 reference statements)
3
67
0
Order By: Relevance
“…An earlier study suggested that EMT and the invasiveness induced by KLF5 knockdown depend on the mutation or ablation of p53 in esophageal squamous cell carcinoma (11). In HaCaT cells, both alleles of p53 are mutated, which extends the p53 half-life and disrupts its DNA binding activity (87).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study suggested that EMT and the invasiveness induced by KLF5 knockdown depend on the mutation or ablation of p53 in esophageal squamous cell carcinoma (11). In HaCaT cells, both alleles of p53 are mutated, which extends the p53 half-life and disrupts its DNA binding activity (87).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular migration, for example, appears to be regulated by KLF5 in a context-dependent manner (6,9,10), as KLF5 promotes cell migration in mouse primary esophageal keratinocytes by inducing the integrin-linked kinase (ILK) (10). Loss of Klf5 could drive invasive progression of human squamous cell cancer in the context of p53 ablation (11). The migratory ability of cells is often associated with epithelial-mesenchymal transition (EMT) during normal development and cancer progression (12), and KLF5 was predicted to be 1 of the 25 potential regulators of EMT predicted by a novel statistical method, NetworkProfiler, which predicts specific gene regulatory networks for a specific tumor characteristic on the basis of gene expression data (13).…”
mentioning
confidence: 99%
“…11 Biotinylated species-specific secondary antibodies (Vector Laboratories) were added, and antibody binding was detected with the Vectastain Elite ABC Kit (Vector Laboratories) and DAB Peroxidase Substrate Kit (Vector Laboratories), followed by counterstaining with hematoxylin. KLF4 expression was scored using the following scale, as previously described 50 : 0, no staining; 1, very weak staining; 2, weak staining; 3, moderate staining; 4, strong staining; and 5, very strong staining. For each normal tissue, high-grade dysplasia, or invasive ESCC, 100 cells were scored.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Considering ESCC, however, KLF5 might play a tumor suppressor role. Downregulation of KLF5 might reduce its limitation on NOTCH1 activity and is sufficient on its own to transform primary human keratinocytes to form invasive tumors in the context of P53 mutation or loss of function (41). KLF5 might also activate the JNK pathway and lead to apoptosis and reduced cell survival (42).…”
Section: Discussionmentioning
confidence: 99%